Zginanie Pasma i Półpasma Rusztowego - Husiar, B.; Świtka, R. (Engineering Transactions, 1972)
In the paper Considered is a regular grid having the form of a strip or a semi-strip. The problem of bending of a grid is described by a system of two partial difference equations for two unknowns: the deflections of the grid nodes and the interactions between the beams at the nodes. The solution is obtained by means of the finite, discrete eigentransformation and a discrete Fourier transformation. The solutions are derived for an infinite strip with hinged transversal beams, and for a semi-strip with the transversal edge being hinged, built-in or free. Various kinds of loadings are taken into consideration; the method applied is illustrated by numerical examples and graphs.